The Genus Caulerpa from Central Visayas, Philippines. - Menez, Ernani G.; Calumpomg, Hilconida P. (Washington, D.C., USA Smithsonian Institution, 1982)
Smithsonian Contribution to the marine sciences; no.17
Keywords: Botany; Caulerpa